Nanotechnology in herbal medicines and cosmetics - Sahu A.N. (My University, 2025)
Nanophytomedicines are prepared from active phytoconstituents or standardized extracts. The world market for nanomedicine is estimated to reach $130.9 billion by the fiscal year 2016. Liposome nanoparticle (NP) with entrapped doxorubicin has been reported to be 300 fold more effective because of better pharmacokinetic ability in treatment of Kaposi sarcoma. NP of paclitaxel is used in the treatment of breast cancer. It has increased water solubility, reduced toxicity and improved therapeutic index. Nanotized herbal drug containing active principles of veteh root, seawort, cassia twig and liquorice root is found to be effective in pulmonary, liver, bone, brain and skin cancer. The in-vivo pharmacokinetic parameters of polymeric nanoparticles containing curcumin reveal at least 9 fold increase in oral bioavailability when compared to curcumin administered with piperine as absorption enhancer. The green nanotechnology utilizes plant based phytochemicals in the overall synthesis and architecture of NP. Cumin and gum arabic are used for synthesis of gold NP that has reduced toxicity to living organism and environment. Bhasma used in Ayurveda is ancient but ultra modern nanomedicine prepared from metal. Swarna bhasma has particle size of 56 nm. NP in cosmetics has been used safely and effectively. NP ingredients like Zno and TiO2 have properties that provide greater degree of protection from sun. Liposome containing Aloe vera extract in size range less than 200 nm diameter has shown higher rate of cell proliferation and increased synthesis of collagenase in in vitro test using human skin fibroblast and epidermal keratinocytes.